WHAT GETS INSIDE: Violent Entanglements and Toxic Boundaries in Mexico City - ROBERTS, ELIZABETH F. S. (Cultural anthropology, 2017)
Entanglement is a key concept in contemporary anthropology and science and technology studies. By tracing the contingent and uncertain relations that endow objects with seemingly stable boundaries, entanglement allows us to see how such boundaries restrict our ability to know the world better. This article examines the concept of entanglement in the context of contemporary life in a working-class Mexico City neighborhood, Colonia Periférico, and a longitudinal environmental health project that studies the neighborhood’s residents. While entanglement has its uses, the entanglement of working-class bodies with globalizing processes like NAFTA and the ongoing War on Drugs shows that the concept has its limits. For working-class residents, life is already deeply entangled with chronic economic and political instability shaped through the violent ravages of transnational capital. Instead, I trace how residents in Colonia Periférico secure stability through toxic boundaries that protectively keep out the disruptive effects of police and public health surveillance. Colonia Periférico’s boundaries, which include a sewage-filled dam, cement dust, and freeway exhaust, are clearly entangled with residents’bodies. They get inside. These entanglements are the price paid for a remarkable stability, in which children can play on the streets and attentive care for drug-addicted and disabled residents is part of everyday life. With the goal of knowing the world better, then, we might complicate celebratory calls for the uncertainty of entanglement by taking into account both the practices that make boundaries and what boundaries have to offer.